Enhances production of coffee (Coffea robusta): The role of pollinator, forages potency, and honey production from Tetragonula sp. (Meliponinae) in Central Lombok, Indonesia - Bambang Supeno; Erwan Erwan; Agussalim Agussalim (Society for Indonesian Biodiversity, 2021)
Abstract. Supeno B, Erwan, Agussalim. 2021. Enhances production of coffee (Coffea robusta): The role of pollinator, forages potency, and honey production from Tetragonula sp. (Meliponinae) in Central Lombok, Indonesia. Biodiversitas 22: 4687-4693. The bees role as an agent of pollinators to improve the productivity of plants. This study was purposed to enhance coffee production (Coffea robusta) by roles of stingless bee Tetragonula sp. as pollinator agent, forages potency, and honey production. This study has been conducted in a coffee plantation in Lantan, Central Lombok, Indonesia. Several parameters were measured such as the number of bunches and flowers, production of nectar and pollen, sucrose nectar content, production of coffee, production of honey, honey stomach volume, and pollen weight. The results showed that the different observation time influenced the number of bunches, flowers, production of nectar and pollen, sucrose nectar content (P<0.01). The number of bunches ranged from 58.2 to 144.9 bunches/tree, the number of flowers 36.3 to 58.7 flowers/bunches, and 2,362.5 to 8.250.6 flowers/tree. Furthermore, the nectar production 9.16 to 33.85 g/tree, pollen production 1.72 to 5.95 g/tree, sucrose nectar content 20.6 to 35.0%. Estimation of coffee production before pollinated by Tetragonula sp. was 1,230.8 kg/ha, but after pollination by Tetragonula was increased it became 3,605.7 kg/ha (49.1%). Fruit production before pollinated by Tetragonula sp. was 2,127.2 fruit/tree, but after pollination by Tetragonula sp. increased to 8,309.2 fruit/tree (59.2%). Production of honey from Tetragonula sp. was 3.74 g/hive/5 months and in Apis cerana was 301.35 g/hive/5 months. It can be concluded that the Tetragonula sp. as an agent of pollinators can enhance the production of coffee and increase the biodiversity of coffee.